HLA-DR typing in coeliac disease: evidence for genetic heterogeneity. Issue 6458 (8th December 1984) - Ellis, A; Taylor, C J; Dillon-Remmy, M; Woodrow, J C; McConnell, R B
Abstract : Sixty nine propositi from a family study of coeliac disease were typed for HLA-DR antigens. Sixty three (91%) were found to carry the antigen DR3, which was a significantly greater proportion (p = 9.6 X 10(-24] than among the 168 controls (26%). Concurrently 42 children with the disease were DR typed. Not only was the frequency of DR3 significantly increased in these patients (86% versus 26% in controls; p = 3.1 X 10(-12] but so also was the frequency of DR7 (patients 60%, controls 29%; p = 5.8 X 10(-4]. When those propositi whose coeliac disease presented before the age of 20 were combined with the childhood coeliac group and a comparison made between these patients and the remainder of the propositi, all of whom presented when they were older than 20, the childhood onset group had a significant excess of DR7 (p = 2.2 X 10(-3] and a significant deficiency of DR2 (p = 3.5 X 10(-3]. These findings indicate that childhood coeliac disease and adult coeliac disease are genetically heterogeneous.